PERILAKU GAMBLER FALLACY DALAM MENGELOLA KEUANGAN PRIBADI (SUATU KAJIAN PUSTAKA) - Sina, Peter Garlans (Jurnal Ilmiah Econosains, 2013)
Abstract The aim of this research is to provide evidence of gambler fallacy behavior in a personal financial management which could impede the achievement of financial freedom such as managing the expenditure and saving inaccurately. By developing a comprehensive understanding that the value of probability is equal for both the expected and not expected events and not creating a financial decision in a hurry are the ways in reducing the problem. Keyword : gambler fallacy, personal finance, spending, saving